Korrektur og retning som leksikografiske funktioner - Tarp, Sven (HERMES - Journal of Language and Communication in Business, 2004)
Thousands of people, in private or public companies and institutions, are daily engaged in text revision or marking. These people frequently run into problems of different types which can be solved by means of dictionary consultation. But surprisingly, lexicographic theory has only sporadically dealt with this whole problematic and no serious attempt has been made in order to overcome the hurdle. In this article, text revision and marking are analysed as user situations within the framework of the functional theory of lexicography. The article shows that both text revision and marking are closely related to text production in the mother tongue, text production in a foreign language and translation from and into the mother tongue. It concludes, however, that the users’ needs in these user situations and the corresponding lexicographic data are slightly different from the needs and data in terms of revision and marking. Consequently, it recommends that these data are included in future dictionaries for text production and translation in order to conceive them in conformity with the needs of this speciﬁc group of users.